EFEKTIVITAS PENGGUNAAN MEDIA ISPRING SUITE 8 TERHADAP HASIL BELAJAR SEJARAH KELAS X SMAN 5 PONTIANAK - Damayanti, Evi; Rustiyarso, Rustiyarso; Rahmatika, Ika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the effectiveness of using media iSpring Suite 8 to student learning outcomes in history subject of class X IPS SMA Negeri 5 Pontianak. The method of research used experimental with quasi experimental type nonequivalent control group design. The subject of this researchÂ was the X IPS class of SMA Negeri 5 Pontianak. The X IPS 1 as an experimental class and X IPS 3 as a control class which amounted each class is 37 students. The research instrument in this research used the form of multiple choice test with 30 questions. Based on the result of research, the average post-test of control class was 69,05 while for the experimental class, the average was 84,57. The results of the hypothesis test analysis, obtained the significance of the post-test value is 0,000 <0,05, so it is said that Ho is rejected and Ha is accepted and the results of the calculation of the effect size (ES) is 0,88. The conclusion that using of media iSpring Suite 8 is effective in improving student learning outcomes in history subjects of class X IPS SMAN 5 Pontianak.Â Keyword: Effectiveness, media iSpring Suite 8, learning outcomes, history subject, SMA Negeri 5 PontianakÂ